PENGARUH EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP FRAUD PADA BANK SYARIAH MANDIRI CABANG AHMAD YANI BANDUNG - Nur’aeni Nur’aeni (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: The main objective of this study was to analyze the influence of the effectiveness of internal control systems against fraud, to analyze the influence of the quality of human resources against fraud, and to analyze the influence of the effectiveness of internal controls and the quality of human resourcess imultaneously to fraud on the Bank Syariah Mandiri Branch Ahmad Yani Bandung. The usefulness of this research was to obtain empirical answer to the hypothesis that the proposed research, and can be a useful and positive   Bank Syariah Mandiri Branch Ahmad Yani Bandung author smade ​​the object of research. The study was conducted using a quantitative approach. This type of data is grouped into two categories: primary data and secondary data. Based on the test results of the t test, for variables X1 obtained t > t table (2.906 > 2.052) and sig = 0.007 < 0.05 then Ho is rejected, meaning that the partial effectiveness of internal control systems affect the fraud. For X2 obtained t > t table (2.192 > 2.052) and sig = 0.037 < 0.05 then Ho is rejected, meaning that partially affect the quality of human resources against fraud. Based on the results of test calculations obtained f of F (6.808) > F (3.35), and sig = 0.004 < 0.05; then Ho is rejected, it means simultaneously effectiveness of internal control systems and the quality of human resources affect the fraud. Keywords: Effectiveness of Internal Control Systems, Quality of Human Resourcess, Fraud